Kawaii, kenosis, Verwindung: A reading of kawaii through Vattimo's philosophy of 'weak thought'. Issue 1 (1st April 2016) - Botz-Bornstein, Thorsten
Kawaii is different from the western cute because it may also include 'cool'. The paradoxical coexistence of weakness and strength, of cute and cool, is interesting in philosophical terms. Kawaii is not simply weak but equipped with its own kind of strength. In this article, I explore kawaii by using philosophical ideas linked to the paradigm of 'strength out of weakness' that appears in the so-called 'weak thought' philosophy of Gianni Vattimo. The Heideggerian term Verwindung (twisting) as it is used by Vattimo, is at the centre of this analysis. Vattimo's philosophy is also based on the Christian idea of kenosis, a classic theological term that can be translated as 'weakening'. Feminist theologians use the concept of kenosis in order to 'feminize' theology. It is in this context that kawaii can be shown as bringing together such antagonistic qualities as submission and subversion. Vattimo's Verwindung describes the effect of distortion to which gender distinctions are submitted through the impact of kawaii. As a result, kawaii should be seen as femininity without metanarratives because kawaii strips feminist gestures of their metaphysical features.